From Abandoned Land to Economic Hub: Assessing the Revitalization of Beran Field, Bangunsari Village, Indonesia - Fitriani, Hanik (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
The revitalization of the Beran Field in Bangunsari Village, Dolopo District, and Madiun Regency has transformed an abandoned area into a vibrant public space and tourist destination, significantly impacting the welfare and economy of the local community. This study analyzes the strategies implemented by the local government, the forms of revitalization undertaken, and the resulting effects on the community. The two-stage revitalization process involved physical interventions such as the construction of a jogging track, playground, and improved facilities. The establishment of the